Local organization of Social Services and K wave theory - Bódi, Ferenc (Acta Medicinae et Sociologica, 2021)
Wars are followed by periods of peace, crises by longer periods of economic prosperity. Economy has cycles like seasons that alternate in historical time. On the basis of Kondratiev’s theory, Schumpeter claims that previous production technologies are replaced in a form of creative destruction. Human capital, which determines the development of the economy, also has a development cycle. Human investments precede the period of creative destruction taking place in the economy, facilitating the change on the one hand and they are a part of the change on the other hand. Local Organization of Social Services (LOSS), including education, have a key role to play in these creative cycles. Historical examples show changes in the human capital cycle are not a function of blind luck. On the contrary, any major change was preceded by a well-thought-out political decision made by politicians who defined the era.